2019
DOI: 10.1016/j.bbmt.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Microbiome and Mycobiome Changes during Autologous Transplantation for Multiple Myeloma: Results of a Prospective Pilot Study

Abstract: Microbiome dysbiosis has been associated with adverse outcomes of hematopoietic cell transplantation (HCT). We hypothesized that exposure to high-dose melphalan and antimicrobials in patients undergoing autologous HCT for plasma cell disorders results in oral and gastrointestinal microbial dysbiosis, which in turn is associated with regimen-related toxicities. We conducted a prospective study describing the longitudinal changes in oral and gastrointestinal bacteriome and mycobiome in this patient population. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 27 publications
1
35
1
Order By: Relevance
“…These observations are consistent with previous single-center analyses of 8, 15, and 28 patients each. 25,43,44 Importantly, we observed that patients with greater degree of microbiome damage, as assessed by below-median fecal diversity around the time of neutrophil engraftment, had higher rates of progression following transplantation.…”
Section: Discussionmentioning
confidence: 69%
“…These observations are consistent with previous single-center analyses of 8, 15, and 28 patients each. 25,43,44 Importantly, we observed that patients with greater degree of microbiome damage, as assessed by below-median fecal diversity around the time of neutrophil engraftment, had higher rates of progression following transplantation.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, patients with a baseline microbiome community dominated by Candida and aciduric bacteria were more likely to develop oral candidiasis during antineoplastic treatment (9). Recently, variation in mycobiome composition was linked to treatment-related toxicities after autologous HSCT for multiple myeloma (10). Specifically, the composition of the baseline oral mycobiome was associated with vomiting as well as culture-negative neutropenic fever, while the fungal community on day 7 posttransplantion was associated with the incidence and severity of mucositis.…”
mentioning
confidence: 99%
“…In addition to chemotherapy, antimicrobial therapy, a very common practice in this patient population, impacts mycobiome composition. For example, it was observed that antibiotics with antianaerobic activity affected the oral fungal community composition posttransplantion in multiple myeloma patients (10). Also, bacteremia with fluconazole-resistant Candida has been associated with exposure to several different antimicrobials, including carbapenems, clindamycin, and colistin (15).…”
mentioning
confidence: 99%
“…In addition, it will be important that the myeloma research community continue to conduct smaller studies using other methodologies such as molecular-based tools to explore the immune microenvironment and identify novel immune signatures that may be associated with response or outcomes. Recent data from studies exploring the gastrointestinal microbiome suggest that we need to expand our scope beyond peripheral blood and bone marrow studies when evaluating the IP [64,65].…”
Section: Milestones and Deliverablesmentioning
confidence: 99%